Development of Family Empowerment Model in Diabetes Management Among Type 2 DM Patients - Trisnadewi, Ni Wayan; Januraga, Pande Putu; Pinatih, Gde Ngurah Indraguna; Duarsa, Dyah Pradnyaparamita (Public Health of Indonesia, 2024)
Background: Diabetes management has not been optimally implemented by patients, considering the high incidence of diabetes complications. Therefore, family empowerment is important for diabetes management. Objective: This study aims to determine factors related to diabetes management, inhibiting, and supporting factors for diabetes management to develop a family-based educational model in diabetes management through expert testing.Methods: This research used Mixed Methods design with an Explanatory Sequential Design approach. A cross-sectional approach to 207 people with DM selection using a multistage sampling technique. Data was collected by questionnaire, in-depth interview, and Delphi study. Data analysis using chi-square and logistic regression. The development of family empowerment model is based on the theory Ladder of Empowerment, Social Cohesion, and Family Support. Results: Research results showed that good knowledge of patients, good family empowerment, and absence of DM risk factors are related to diabetes management. Model development and expert testing (Delphi Study) of the model find that a family-based diabetes management module is needed. Conclusion: A good family-based diabetes management module includes aspects of Self-Instructional, Self-Contained, Stand Alone, Adaptive, and User-Friendly aspects. This module is expected to improve diabetes management for patients and their families so that diabetes complications can be prevented and the patient's quality of life increases.